S-palmitoylation regulates the function of the mitochondria-associated endoplasmic reticulum membrane to alleviate the senescence of nucleus pulposus cells - Qi Liang; Jianfeng Zhang; Jingchuan Yan; Weidong Guo; Jian Zhao; Li Lin; Shuang Li; Daxiong Feng; Bo Liao (PLoS ONE, 2026)
Intervertebral disc degeneration (IVDD) is the primary cause of spinal degenerative diseases. Nucleus pulposus (NP) cell senescence is a significant pathological manifestation of IVDD. Here, we constructed a hypoxia-induced NP cell model to clarify the mechanisms by which S-palmitoylation is involved in NPC senescence. The IP3R S-palmitoylation of NP cells was significantly reduced under hypoxic conditions, contributing to abnormalities in mitochondria-associated membranes (MAMs). The study found that cellular expression of Bax, Bcl-2, Cleaved-Caspase8, Cleaved-Caspase3, MMP3, and MMP13 was promoted, while COL2 and AGG expression was inhibited. The up-regulated palmitoylation-modifying enzyme DHHC6 can promote IP3R S-palmitoylation modification and regulate GRP75, VDAC1, Drp1, and Mfn2 expression. It can inhibit apoptosis in NP cells, reduce intracellular calcium and ROS levels, elevate mitochondrial membrane potential, and reduce γ-H2AX expression levels. It also inhibited the protein expression levels of hypoxia-induced apoptosis molecules, matrix-degrading enzymes, and up-regulated extracellular matrix protein expression. These results suggested that hypoxia-induced IP3R depalmitoylation might play a role in structural and functional abnormalities in MAMs, which trigger senescence in NP cells.